Towards an Ecology of Encounter in Kathleen Jamie’s Selected Poems - Alkass Yousif, Dr. Anan (Al-Adab Journal, 2020)
One of the global and crucial concerns of the twentieth and twenty-first centuries is the ecological preservation of the life-supporting system of the earth. It is considered one of the most important current studies that challenge the rapid degradation of the environment and wildlife. The purpose of this paper is to explore Kathleen Jamie’s (1962) vital ecological vision that she conveys through her ecopoetry and some of her nonfiction writings, arguing that developing ecological consciousness is crucial not merely to rediscover the value of natural world but also to realize that it is another form the human self. The paper also argues that ecological degradation as revealed by Jamie's ecopoetry paradoxically stands as the very reason that would foster the ecology of mind to observe the natural world as a valuable entity in itself. Jamie’s literary output extends to generate citizens of the natural world, a world that is based on comprehending the interconnectedness and interdependence between people and their physical landscape. Otherwise, the contemporary individual would be inclined to live in self-isolation.To examine Jamie’s portrayal of the relationship between man and his environment, ecocriticism is employed as an interdisciplinary approach that emerged in the 1980s to interrogate man’s patterns of relationships with nature, questioning the common notions of belonging and dwelling. In so doing, ecopoetry is demonstrated as essential in cultivating a new canon of nature poetry that promotes a maneuver beyond the politics of place and the limitation of nationhood.Jamie is a prominent contemporary Scottish poet who endeavors not only to promote ecological consciousness but also to advocate a breakdown of all the barriers between the human and non-human world, man's individual 'I' and the assumed 'Otherness' of nature. It is the construction of a new poetic and ecological mode towards an ecology of encounter, a path towards empathy between man and nature that would render the former more human and the latter more natural.